Novel ketamine and zinc treatment for anorexia nervosa and the potential beneficial interactions with the gut microbiome. (May 2023) - Elwyn, Rosiel; Mitchell, Jules; Kohn, Michael R.; Driver, Christina; Hay, Phillipa; Lagopoulos, Jim; Hermens, Daniel F.
Abstract: Anorexia nervosa (AN) is a severe illness with diverse aetiological and maintaining contributors including neurobiological, metabolic, psychological, and social determining factors. In addition to nutritional recovery, multiple psychological and pharmacological therapies and brain-based stimulations have been explored; however, existing treatments have limited efficacy. This paper outlines a neurobiological model of glutamatergic and γ-aminobutyric acid (GABA)-ergic dysfunction, exacerbated by chronic gut microbiome dysbiosis and zinc depletion at a brain and gut level. The gut microbiome is established early in development, and early exposure to stress and adversity contribute to gut microbial disturbance in AN, early dysregulation to glutamatergic and GABAergic networks, interoceptive impairment, and inhibited caloric harvest from food (e.g., zinc malabsorption, competition for zinc ions between gut bacteria and host). Zinc is a key part of glutamatergic and GABAergic networks, and also affects leptin and gut microbial function; systems dysregulated in AN. Low doses of ketamine in conjunction with zinc, could provide an efficacious combination to act on NMDA receptors and normalise glutamatergic, GABAergic and gut function in AN. Graphical Abstract: ga1 Highlights: Neurobiological model for a proposed novel treatment for anorexia nervosa. Early exposure to stress and adversity dysregulates key neurobiological systems in AN. Chronically dysregulated systems in the brain and gut may maintain long-term illness and treatment non-response. Low-dose oral ketamine and zinc in combination may restore function in these domains.